Exploring the Role of Family Financial Education and Lifestyle on Financial Management Behavior: The Mediating Effect of Financial Self-Efficacy - Rufaidah, Meylinda; Setiyono, Wisnu P. (Indonesian Journal of Public Policy Review, 2023)
This quantitative study investigates the influence of financial literacy, family financial education, and lifestyle on financial management behavior, with a focus on the mediating role of financial self-efficacy. A purposive sampling technique was used, resulting in 105 employed respondents. Data was collected through questionnaires and analyzed using path analysis in the SmartPLS application. The findings indicate that financial literacy does not directly impact financial management, but family financial education significantly influences financial management behavior, both directly and through financial self-efficacy. While lifestyle does not have a direct effect, it exerts a significant influence on financial management behavior through financial self-efficacy. These results have implications for promoting effective financial education within families and fostering financial self-efficacy to enhance overall financial management behavior in communities. Highlights: Family financial education: Examining the significant influence of family financial education on financial management behavior in society, emphasizing the importance of imparting financial knowledge and skills within the family unit. Financial self-efficacy: Highlighting the mediating role of financial self-efficacy in the relationship between lifestyle and financial management behavior, underscoring the importance of individuals' belief in their ability to handle financial tasks and make informed decisions. Impact of financial literacy: Discussing the findings that indicate the lack of a direct influence of financial literacy on financial management behavior, shedding light on the need for comprehensive approaches to financial education that go beyond knowledge acquisition to effectively shape financial behaviors. Keywords: Family Financial Education, Financial Literacy, Lifestyle, Financial Management Behavior, Financia Self-Efficacyl